Legality and Legitimacy of the United Nations as a Lawmaking Actor in International Law: A Conceptual and Doctrinal Analysis - Hilton Tarnama Putra M; Atip Latipulhayat; Diajeng Wulan Christianti; Danial Danial; Afandi Sitamala (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2026)
This article examines the potential of the United Nations (UN) as a key actor in the formation of international law. Considering the evolving patterns of contemporary international law, which are increasingly multilateral and no longer entirely state-centered, the role of the UN in norm creation has become increasingly significant. The study emphasizes the importance of addressing not only questions of legality but also legitimacy, to ensure that the UN’s legal outputs can be recognized as valid sources of international law. Methodologically, this article adopts a doctrinal and descriptive analytical approach, focusing on the normative framework of the UN Charter and the practice of selected UN organs. The scope of analysis is limited to the General Assembly, the Security Council, the International Law Commission, and the International Court of Justice, as the principal institutional sites of UN related norm development. The findings suggest that the UN Charter explicitly provides a legal basis for the organization to contribute to international lawmaking. Resolutions, declarations, and other legal instruments produced by the UN, when reflecting universal principles such as humanity, peace, and security, are often regarded as legitimate sources of international lawmaking, although their legal status and normative authority remain subject to ongoing doctrinal debate. Thus, the legitimacy of the UN rests primarily on its teleological dimension-namely, the pursuit of universal purposes while continuing to raise contested questions regarding the limits of its lawmaking authority within the international legal system.